Clinical outcomes after ACL reconstruction with free quadriceps tendon autograft versus hamstring tendons autograft. A retrospective study with a minimal follow-up two years - Adrian Todor; Dan Viorel Nistor; Sergiu Caterev (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this retrospective study was to compare the clinical outcomes of anatomic single bundle ACL reconstruction using either a free quadriceps tendon autograft or a quadrupled hamstring autograft with a minimum follow-up of 24 months. Methods: Consecutive patients undergoing ACL reconstruction using either a free quadriceps tendon autograft or hamstring tendon autograft from January 2013 to December 2014 were included. ACL reconstruction was done in all patients due to isolated ACL tears. Patients with associated cartilage lesions > Outerbridge III, meniscal lesions in need of meniscectomy or repair as well as patients with prior knee surgery on the affected or contralateral knee were excluded. The primary outcome evaluation was the side-to-side difference in instrumented Lachman testing. Secondary outcome evaluation consisted in the Lysholm, modified Cincinnati and SF-36 scores. Side-to-side difference in range of motion and thigh diameter was also documented. Results: After applying the inclusion/exclusion criteria, a total of 82 patients were identified and 72 (87.8%) presented to the hospital for follow-up. There were 39 patients with quadriceps graft (30.64 ± 8.71, range: 18–53 years) and 33 patients with hamstrings (28.60 ± 6.74, range: 18–46 years). No statistically significant difference between groups was detected with regard to KT-1000 measurements (p = 0.326). No significant difference was found between the mean postoperative Lysholm (p = 0.299), the modified Cincinnati (p = 0.665) and the general SF-36 scores between groups (p = 0.588). Less side-to-side thigh diameter difference was noted in the quadriceps graft group (p = 0.026). Conclusion: In conclusion, similar clinical results, in terms of stability and subjective measures, can be obtained after ACL reconstruction both with a free quadriceps and a 4-strand hamstring tendons autograft. Level of evidence: Level III, Therapeutic Study. Keywords: ACL reconstruction, Quadriceps graft, Hamstring graft, Single bundle, Clinical outcome